A Novel KPC Variant KPC-55 in Klebsiella pneumoniae ST307 of Reinforced Meropenem-Hydrolyzing Activity - Yoon, Eun-Jeong; Choi, You Jeong; Park, Sun Hee; Shin, Jeong Hwan; Park, Sung Gyun; Choi, Jong Rak; Jeong, Seok Hoon (Frontiers in Microbiology, 2020)
A novel Klebsiella pneumoniae carbapenemase (KPC) variant, KPC-55, produced by a K. pneumoniae ST307 strain was characterized. K. pneumoniae strain BS407 was recovered from an active surveillance rectal swab of a patient newly admitted to a general hospital in Busan, South Korea. Carbapenemase production was confirmed by the modified Hodge test, and the MICs of β-lactams were determined by the broth microdilution method. The whole genome was sequenced. Cloning and expression of the blaKPC-55 gene in Escherichia coli and MIC determination were performed. The enzyme KPC-55 was used for kinetic assays against β-lactams and compared with the KPC-2 enzyme. The new allele of the blaKPC gene had a T794A alteration compared to the blaKPC-2 gene, resulting in the amino acid substitution Y264N in the middle of the 9-sheet. Compared to the KPC-2-producing strain, the KPC-55-producing strain exhibited a lower level of resistance to most β-lactam drugs tested, however, the KPC-55 enzyme catalyzed aztreonam and meropenem at an increased efficiency compared to the catalytic activity of KPC-2. KPC subtypes could have varied phenotypes due to alterations in amino acid sequences, and such an unexpected resistance phenotype emphasizes the importance of detailed characterizations for the carbapenemase-producing Enterobacterales.